International Governance and China’s Path to Nuclear Discharge in Japan - Zhengyan Zuo (Law and Economy, 2024)
Japan’s plan to discharge a huge amount of nuclear sewage into the ocean may jeopardize the overall interests of all mankind, the national interests of all countries, and the interests of individual citizens. The current international nuclear pollution control treaty system has some regulations on Japan’s behavior, but there are also many shortcomings in the legal system of marine nuclear pollution control, such as fragmentation of the legal system of marine nuclear pollution control, insufficient binding force of the existing rules on the control of international nuclear pollution, difficulties in the pursuit of responsibility for marine nuclear pollution, and ineffectiveness of the international cooperation on the control of marine nuclear pollution. Ineffective international cooperation in the governance of marine nuclear pollution. In this regard, under the guidance of the concept of the community of maritime destiny, China needs to comply with the existing international rules, and at the same time do a good job in the comprehensive rule of law strategy plan that combines legal, diplomatic and public opinion means.[1] [1] Luo Huanxin, (2021). A Comprehensive Legal Interpretation of Japan’s Nuclear Sewage Discharge: A Comprehensive Analysis of Liability Provisions in International and Domestic Law. The Japan Journal, (04), 35-61+145+149.